2021
DOI: 10.1073/pnas.2104666118
|View full text |Cite
|
Sign up to set email alerts
|

The iron chaperone and nucleic acid–binding activities of poly(rC)-binding protein 1 are separable and independently essential

Abstract: Poly(rC)-binding protein (PCBP1) is a multifunctional adaptor protein that can coordinate single-stranded nucleic acids and iron–glutathione complexes, altering the processing and transfer of these ligands through interactions with other proteins. Multiple phenotypes are ascribed to cells lacking PCBP1, but the relative contribution of RNA, DNA, or iron chaperone activity is not consistently clear. Here, we report the identification of amino acid residues required for iron coordination on each structural domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The depletion of GSH can not only inactivate GPX4 but also mobilize Fe(II) for Fenton chemistry, promoting the propagation of lipid peroxides and ultimately ferroptosis. In addition, iron storage in ferritin requires the formation of the GSH-iron complex, which is delivered to ferritin via the chaperone poly(rC) binding protein 1 (PCBP1) (Patel et al, 2021). Thus, depletion of GSH promotes the availability of labile iron.…”
Section: Iron Regulation: Iron-driven Lipid Peroxidationmentioning
confidence: 99%
“…The depletion of GSH can not only inactivate GPX4 but also mobilize Fe(II) for Fenton chemistry, promoting the propagation of lipid peroxides and ultimately ferroptosis. In addition, iron storage in ferritin requires the formation of the GSH-iron complex, which is delivered to ferritin via the chaperone poly(rC) binding protein 1 (PCBP1) (Patel et al, 2021). Thus, depletion of GSH promotes the availability of labile iron.…”
Section: Iron Regulation: Iron-driven Lipid Peroxidationmentioning
confidence: 99%
“…In the absence of hnRNP E1, repair at poly-C sites slows down because signaling and loading of repair proteins is slow; however, other proteins such as RPA carry out the functions of hnRNP E1 directly at these sites in DNA repair. While the manuscript was being revised a new publication showed that the iron-binding and DNA damage functions are separable from RNA binding functions ( Patel et al, 2021 ); the authors also suggested that the nucleic acid and iron binding by hnRNP E1 might enhance the assembly or repair of iron cofactors in DNA- and RNA-modifying enzymes. Although this is a major possibility in untreated E1KD cells, we predict the existence of additional possibilities; in addition, sensing and repair of genotoxin-induced DNA damage may involve different mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulating intracellular iron trafficking, PCBPs are involved in post-transcriptional gene regulation, maintenance of mitochondrial stability, and are associated with a wide variety of pathophysiologies such as rheumatoid arthritis [ 37 ], amyotrophic lateral sclerosis (ALS) [ 38 ], and Huntington’s disease (HD), and certain neurodevelopmental disorders [ 39 ]. Although the iron chaperone and RNA-binding functions of PCBPs have been shown to be independently essential [ 40 ], it is not clear how these functions potentially contribute to the pathogenesis of the above-mentioned disorders.…”
Section: Cytosolic Chaperones For Delivering Iron Into Ferritinmentioning
confidence: 99%